Building Community-Based Models for Climate Resilient Agriculture and Fisheries Across Landscapes within the Municipality of Ivisan, Capiz - International Institute of Rural Reconstruction (2017)
A recent Inter-governmental Panel on Climate Change (IPCC) report states that climate change is unequivocal and its immediate impact is the modification of the worlds’ biophysical and natural systems resulting to changes in interspecies dynamics, movement of range, altered abundance, and shift in seasonal activities in various ecosystems. Agriculture will be the hardest hit sector globally as its productivity is primarily based on the integrity of agro-ecosystems. Adverse impacts to agriculture will have direct impacts on livelihoods, food security, and nutrition in rural areas. Climate resilient or smart agriculture (CRA/CSA), as a climate change response, provides an option for resource poor farmers in rural areas through its three- tiered objectives, which are: (a) increasing agriculture productivity and income in a sustainable, environmentally sound manner; (b) building capacity of households and food systems to adapt to climate change; and (c) reducing emissions of Greenhouse Gases (GHG’s) while increasing carbon sequestration of agro-ecosystems. Healthy landscapes support food security, livelihoods, and ecosystem functions (helping build resilience). Global knowledge and experience on CRA/CSA is already vast. IIRR believes that its greater adoption by small-holder farmers, especially in the Philippine context, could be facilitated and accelerated, if and when, interventions are coordinated and done through community-based approaches. Communitybased participatory adaptation will be facilitated if interventions are undertaken through multiscalar and multisectoral approaches, with public and private actors converging their services at community and sub-national levels.